1992
DOI: 10.1159/000147227
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide-Like Immunoreactivity in the Human Small Intestine

Abstract: Calcitonin-gene-related-peptide (CGRP)-like immunoreactivity was localized in nerve fibres, neuronal somata and in mucosal endocrine cells of the human small intestine. Immunoreactive enteric neurons were more numerous in the submucous plexuses than in the myenteric plexus. Morphologically, they predominantly had the appearance of type II neurons. The majority of the CGRP-like immunoreactive nerve fibres ran within the ganglionic nerve plexuses. Only a small proportion could be observed in the lamina propria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 8 publications
4
36
1
Order By: Relevance
“…Additionally, immunoreactivity to CGRP was found in endocrine cells in the human small intestine [5,19,21]. In the present study, CGRP was found in tissues of the large intestine obtained from patients suffering from intestinal cancer.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, immunoreactivity to CGRP was found in endocrine cells in the human small intestine [5,19,21]. In the present study, CGRP was found in tissues of the large intestine obtained from patients suffering from intestinal cancer.…”
Section: Discussionsupporting
confidence: 62%
“…In physiological conditions, within nervous structures supplying human large intestines the presence of vasoactive intestinal polypeptide (VIP), calcitonin gene related peptide (CGRP) and neuropeptide Y (NPY) was found [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies have demonstrated the expression of CGRP in neurons and nerve fibres in the submucous and myenteric plexuses in the human small intestine [12] as well as in the small and large intestine of guinea pig and pig [27][28][29][30][31]. Immunohistochemical colocalization investigations have revealed that in the submucous plexuses, CGRP is expressed by local sensory neurons or cholinergic secretomotor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations performed under physiological conditions have demonstrated the expression of vasoactive intestinal peptide (VIP), neuropeptide Y (NPY), pituitary adenylate cyclase-activating polypeptide (PACAP), somatostatin (SOM), substance P (SP) and calcitonin generelated peptide (CGRP) in nerve elements of the enteric nervous system (ENS) supplying the human large intestine [1,[6][7][8][9][10][11][12][13]. Some studies have also revealed profound morphological and functional changes in the ENS associated with pathological conditions of the colon [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…After sympathetic effects are eliminated, MN stimulation causes a contraction that is abolished by capsaicin and is probably due to the release of either substance P or calcitonin gene-related peptide (Barthó & Holzer, 1985;De Luca & Rand, 1990). These nerves do not appear to innervate the muscle layers directly (Gibbins et al 1985;Timmermans et al 1992). Furthermore, contractions of the circular muscle due to capsaicin-induced transmitter release from extrinsic primary afferent nerves are abolished by TTX (Barthó et al 1994).…”
Section: Excitatory Effects Of Mn Stimulationmentioning
confidence: 99%